Politics in Brazil, 1930-1964 an experiment in democracy - Skidmore, Thomas E. (Oxford University Press, 2007)
A study of Brazilian politics from 1930 to 1964, this book begins with Getulio Vargas' 15-year-rule & traces the following years of economic difficulty & political turbulence, culminating in the coup d'etat that overthrew the constitutional government of President Joao Goulart & changes the nature of Brazils' political institutions.